Analysis of Government Regulation’s Response on Sharing Principles - E.P. PURNOMO; MIA, ROSMIATI; DYAH , MUTIARIN (International Journal of Psychosocial Rehabilitation, 2020)
The growth of sharing economy business models such as Indonesia’s ride-sharing model is particularly interesting in the context of cities having issues with population growth and expanding density. In the province of Yogyakarta, the significant growth of Go-Jek Business Networks (Start-up) had also helped contribute to the several public responses, both positive and negative. The ride-sharing platform has rapidly embraced the rise of ride-hailing apps to add convenience to people’s lives. However, it disrupts the market and the government which create conditions for a revolutionary change to establish orders. This research using a qualitative descriptive approach to describe the overview of the research objective. The findings of this research show the operation of a ride-sharing business; Go-Jek as an online company that combines benefits to people in terms of accessibility, economic activity and flexibility. However, there are some divisions in the principle of economic sharing that have not yet implemented, which have led to the failure of local governments to regulate economic business sharing in the province of Yogyakarta.